Pengaruh Perceived Usefulness, Perceived Ease of Use, Perceived Cost, dan Self-Regulation terhadap Subscribe Intention Ruangguru - Soraya Rahmah; Terrylina Arvinta Monoarfa; Rizka Zakiah (Indo Publishing, 2026)
This study aims to analyze the influence of Perceived Usefulness, Perceived Ease of Use, Perceived Cost, and Self-Regulation on Subscribe Intention of Ruangguru among senior high school students in DKI Jakarta. The research addresses the gap between Ruangguru's registered users (over 25 million) and the low conversion rate of free users into paying subscribers. A quantitative approach with a survey method was employed through an online questionnaire distributed to 150 respondents selected using purposive sampling. The independent variables consist of Perceived Usefulness, Perceived Ease of Use, Perceived Cost, and Self-Regulation, while the dependent variable is Subscribe Intention. Data were analyzed using multiple linear regression with SPSS. The results indicate that Perceived Usefulness, Perceived Ease of Use, and Self-Regulation have a positive and significant influence on Subscribe Intention, while Perceived Cost has a negative and significant influence. Simultaneously, all four variables significantly influence Subscribe Intention. The Adjusted R² value indicates that the four variables explain a substantial portion of the variation in Subscribe Intention. These findings are expected to contribute theoretically to technology acceptance models and provide strategic insights for Ruangguru's management in designing more effective user conversion programs.